PENERAPAN TEKNIK EDITING FAST CUT UNTUK MEMPERKUAT STORYTELLING PADA FILM “SAMSARA” - I Kadek Purnama; I Made Denny Chrisna Putra; Nyoman Lia Susanthi (CALACCITRA: JURNAL FILM DAN TELEVISI, 2021)
Editing is the process of compiling, reviewing, selecting, then collecting audio and video material during the production process. The role of an editor is very important, where the final result of the editing process is one of the aspects that determine the quality of a film. An editor must also be able to strengthen storytelling in a film. One of the important elements contained in storytelling is the atmosphere of a scene. There are several techniques that can strengthen the atmosphere of a film scene, one of which is the fast cut editing technique, where this technique will be applied to a film entitled